2021
DOI: 10.1098/rspb.2021.0817
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersers shape the pulp nutrients of fleshy-fruited plants

Abstract: The dispersal-syndrome hypothesis posits that fruit traits are a product of selection by frugivores. Although criticized as adaptationist, recent studies have suggested that traits such as fruit or seed size, colour and odour exhibit signatures that imply selection by animal mutualists. These traits imply nutritional rewards (e.g. lipid, carbohydrate), attracting frugivores; however, this remains incompletely resolved. Here, we investigated whether fruit nutrients (lipid, sugar, protein, vitamin C, water conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
(122 reference statements)
0
16
0
Order By: Relevance
“…Seed dispersal responses to changing environmental conditions can be influenced by plant traits, specifically fruit and seed morphological and biochemical characteristics. Studies have suggested that traits such as fruit or seed size, color and odor influence the way dispersers choose them as food [ 16 ], thereby shaping plant distribution. Here, results revealed a large proportion of studies that mentioned achene, capsule, drupe, fleshy, and nuts as fruit/seed types of many endozoochorous and ornithochorous plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Seed dispersal responses to changing environmental conditions can be influenced by plant traits, specifically fruit and seed morphological and biochemical characteristics. Studies have suggested that traits such as fruit or seed size, color and odor influence the way dispersers choose them as food [ 16 ], thereby shaping plant distribution. Here, results revealed a large proportion of studies that mentioned achene, capsule, drupe, fleshy, and nuts as fruit/seed types of many endozoochorous and ornithochorous plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The single-seeded drupes of L. subcoriacea mature simultaneously in late July and early August (S1 Fig) , and although not documented in the species, are most likely avian-dispersed based on fruit traits [53][54][55] and observations for congeners [34,56]. Although L. subcoriacea has fruits/seeds of similar size to L. benzoin (ovate seeds are 7.02 ± 0.29 mm, n = 101 [37] and 7.02 ± 0.11 mm, n = 50 [57] long, respectively), L. subcoriacea individuals produce fewer fruits than L. benzoin (80 ± 178, n = 290 [37] and 164 ± 104, n = 11 [58], respectively).…”
Section: Study System and Speciesmentioning
confidence: 99%
“…gut passage effects) (Torres et al 2020), post-feeding movements (Tucker et al 2021), environmental conditions of deposition sites (Tochigi et al 2022), fruit morphology, abundance, and seed traits (e.g. size) (Lei et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in propagule traits that affect seed dispersal in plants have been attributed to selection exerted by dispersal vectors (Zhou et al 2013;Lei et al 2021). Seed size is a key trait for seed dispersal, and is pinpointed as one key attribute in the function of these dispersal agents (Ong et al 2022).…”
Section: Introductionmentioning
confidence: 99%